FINANCIAL DISTRESSPROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE BEFORE AND DURING THE COVID 19 PANDEMIC - Joy Elly Tulung; Rakhmat Ramdhany Hunta; Sri Murni (International Journal on Economics, Finance and Sustainable Development, 2022)
The purpose of this study was to determine the difference between the potential for financial distress in property and real estate companies before the covid 19 pandemic and during the covid 19 pandemic. This type of research is a comparative analysis using quantitative methods. The data used is secondary data taken from the official website of the Indonesia Stock Exchange. This study took the population of property and real estate companies listed on the Indonesia Stock Exchange as 33 companies (purposive sampling). The variables used are as many as 2 variables, namely Altman Z score and Zmijewski X Score. The statistical test used in this study is the Paired Sample t-test which aims to find a comparison of two paired groups. Based on the results of the study